Reporting of absolute and relative risk measures in oral health and cardiovascular events studies: A systematic review. Issue 2 (3rd March 2022) - Raittio, Eero; Ashraf, Javed; Farmer, Julie; Nascimento, Gustavo G.; Aldossri, Musfer
Abstract: Objectives: To understand the magnitude of risk of health events, such as cardiovascular diseases (CVD), related to poor oral health, both relative and absolute risk measures should be reported. Our aim was to investigate the extent to which absolute and relative measures of risk are reported in longitudinal studies that assess the association between oral health indicators (OHIs) and CVD. Methods: A systematic search of longitudinal studies investigating the association of any OHI with CVD was carried out using the Embase, Medline and Cochrane library databases. The search covered each database from its inception date to August 2021. Data about reporting relative and absolute risks of the relationship between CVD and OHI from the abstract were extracted. If the relative risk for OHIs and CVD was reported in the abstract, then the underlying absolute risks were searched from the full text, and it was assessed whether it was similarly adjusted for confounding than was the relative risk in the abstract. Results: One hundred‐six articles were included. From these, 85 (80%) studies reported the association of OHIs and CVD with one or more relative risks in the abstract. Of those 85 studies, the underlying absolute risks were accessible or calculable from the abstract or full text of 60 studies. However, of these 60 studies, in only 10 (12%), the underlying absolute risks were similarly adjusted, as were the relative risks in the abstract. The absolute risks of CVD by OHIs were rarely reported without corresponding relative risks in the abstract (n = 2, 2%). Median absolute risk difference in the CVD risk between exposure levels to which the first relative risk in the abstract referred was 1.8% (interquartile range 0.6–4.6, n = 63). Conclusions: Focusing on relative risks over absolute risks was a common practice in literature. Reporting similarly adjusted underlying absolute risks of relative risks was rare in most studies, despite those being helpful for comprehending the magnitude of CVD‐risk increase related to poor oral health. Current reporting practices could lead to an overinterpretation of risk increase of CVD related to poor oral health.